CLINICAL AND LABORATORY EVALUATION OF SHEEP EXPERIMENTALLY INTOXICATED WITH CROTALARIA SPECTABILIS (LEG. PAPILIONOIDEA) SEEDS Evidências clínico-patológicas de ovinos intoxicados experimentalmente com sementes de Crotalaria spectabilis (leg. papilionoidea) - Cifuentes Sanchez, Diana Consuelo; de Medeiros Gomes Simplício, Kalina Mária; Antonio Borges, Lucimara; Fagliari, José Jurandir; Canola, Julio Carlos; Hatayde, Mário Roberto (Revista Acadêmica Ciência Animal, 2013)
The objective of the present study was to evaluate the clinical and laboratory alterations and hepatic lesions caused by the intake of Crotalaria spectabilis in sheep. Fifteen ewes (unknown breed) were used, which were allocated into three groups of 5 animals. These groups received milled C. spectabilis seeds in their feed over 28 days, with inclusion rates of 0.4% (G1), 0.6% (G2) and 1% (G3). Blood samples and hepatic biopsies for histology were drawn at: T0 (day before the seeds were included in the diet), T1 (7 days after the seeds were included), T2 (14 days), T3 (21 days) and T4 (28 days). The results were submitted to variance analysis (ANOVA) using Statistical Analysis System software (SAS), and differences between the means were compared by the Tukey posttest (p < 0.05). Only one animal from G3 presented clinical signs of intoxication at T3. The results from the hematological parameters were within the normal range for this species. Serum activity of aspartate aminotransferase (AST) and creatine phosphokinase(CK) did not show significant differences among the groups, whereas gamma-glutamyltransferase (GGT) activity was significantly different between G1 (33.66 ± 25.8 U/L) and G2 (67.3 ± 14.8 U/L) at T0. Ultrasonography evaluationrevealed hepatic alterations throughout the experimental period, which was confirmed by histology. Therefore, analyses of hemogram and hepatic function alone do not have diagnostic value for C. spectabillis intoxication in sheep, and it is necessary to perform additional tests, such as ultrasonography and percutaneous liver biopsies.